ANALISIS PENGAWASAN PEMBERIAN KREDIT UNTUK MEMINIMALISIR KREDIT BERMASALAH PADA PT. BPR NUSANTARA BONA PASOGIT 14 BOGOR - Mochamad Rizky Mandala Putra; Sari Marliani; July Yuliawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research was conducted with the aim of understanding and analyzing the credit monitoring process to minimize non-performing loans at PT BPR Bona Pasogit 14 Bogor, located at Jalan Raya Puncak Cibogo II KM.74 No.74 No.16 RT 03 RW 05, Cipayung Village, Megamendung District, Bogor Regency, West Java. The study uses a descriptive qualitative approach with triangulation methods, including interviews and field observations. The results of the study indicate that there were errors in the processes and procedures during the granting of credit to debtors, as the staff did not apply the 5C principles. There was a lack of credit monitoring both during the credit granting process and after the credit was given, leading to improper use of the credit by customers. Additionally, certain conditions, such as the COVID-19 pandemic, caused business declines, resulting in debtors being unable to make payments or defaulting, thus leading to non-performing loans.